(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in fostering the growth and progress of the Indian economy, and Rajasthan is no different. In the rural areas of Rajasthan, the MSME sector has been instrumental in generating employment, promoting skill development, and empowering women